Role of banks in sustainable and digital transition - Ryszawska, Bożena (Rola banków w zielonej i cyfrowej transformacji, 2018)
The purpose of this study is to identify how the sustainability and digital transition influence banks. The main thesis can be expressed as follows: sustainability transition and digital transition are changing the role and function of banks, especially the products and services offered by banks. Banks are one of main actors of a broader, multi-level governance designed to support the transition to smart, efficient and low carbon economy. The framework’s structure is based upon the multi-level perspective on socio-technical transitions created by F.W. Geels. The first section of this paper presents the most popular approaches to the problem at hand, as reported in professional literature. Section two presents characteristics of the various actors involved in the anticipated transformation of the economy. The third section discusses the changing roles and frameworks of banks associated with the notion of the broader concept of sustainability and digitalization
Financial Sciences. Nauki o Finansach, 2018, vol. 23, no. 1, s. 65-74
Keywords: sustainable transition; digital transition; banks; zielona transformacja; cyfrowa transformacja w bankowości